Shopping Mall, Consumption Culture And Different Age Group: Review Of Literature In A Sociological Comparative Framework - Verma, Aayushi; Misra, Pawan Kumar (South Asian Journal of Social Sciences and Humanities, 2021)
Many studies had examined the consumption pattern and the way shopping mall is working to satisfy the consumption needs of both young and elderly. This article aims to study consumption culture among different age group. Further it also tries to understand how the social environment and environmental factors of a shopping mall allows for open access to a wide variety of potential participants. Considering various studies, article explores the respective literature and identifies gap for future research. Through a detailed study of theoretical review with focus on different age groups, this study examines ‘elderly’ and ‘young’ and ‘adolescent’ as ‘shoppers’ in consumption spaces. This study contributes to the emerging literature of consumption culture.